Himalayan climes and multispecies encounters
1 online resource.
Keywords: "Woven together as a text of humanities-based environmental research outcomes, Himalayan Climes and Multispecies Encounters hosts a collection of historical and fieldwork-based case studies and conceptual discussions of climate change in the greater Himalayan region. The collective endeavour of the book is expressed in what the editors characterize as the clime studies of the Himalayan multispecies worlds. As a terrestrial concept, the individual clime studies of the authors concretize the abstract concept of climate change in their place- and culturally-specific correlations of weather, climate pattern, and landscape change. Supported by empirical and historical findings, the clime concept in each chapter showcases climate change as clime change. As place, clime is discerned as both a recipient of and a contributor to climate change over time in the Himalayan context. It affirms climate change as multispecies encounters, as part of multifaceted cultural processes, and as ecologically-specific environmental changes in the more-than-human worlds of the Himalayas. As the case studies complement, enrich, and converse with natural scientific understandings of Himalayan climate change, this book offers students, academics, and the interested public fresh approaches to the interdisciplinary field of climate studies and policy debates on climate change and sustainable development"--